Gender representation in animal-related proverbs: Algerian vs. Jordanian Arabic - Madani, Zoubida; Abusalim, Nimer; Rayyan, Mohammad (Frontiers in Sociology, 2023)
Introduction This study explores the connotative meanings in animal-related proverbs used to describe the behavior of men and women in Algerian and Jordanian societies. Methods A questionnaire with 46 Algerian and 45 Jordanian animal-related proverbs was distributed to 30 native Arabic speakers enrolled at the University of Jordan. The analysis focused on adapted categories with a gender perspective, including inferiority, weakness, stupidity, ill-nature, objectification, ugliness, positivity, and shrewdness. Results Both Algerian and Jordanian animal-related proverbs exhibited diverse connotative meanings. Women were predominantly associated with derogatory connotations in both languages, portraying characteristics such as weakness, stupidity, inferiority, cunningness, and trickery. Similar characteristics were present in descriptions of men, but women in Arab cultures were consistently depicted as subordinate and denigrated. Conversely, men were portrayed with authority, control, superiority, and strength over women. Additionally, positive depictions included animals like gazelles, peacocks, partridges, cats, and horses to symbolize the beauty of women. Men's positive characteristics, such as strength, courage, and superiority, were associated with horses, camels, and lions. Discussion This study highlights the prevalent connotations in animal-related proverbs used to describe men and women in Algerian and Jordanian societies. It reveals derogatory portrayals of women, reinforcing their subordinate status, while men are depicted with authority and power. However, positive representations emerged, attributing beauty to women and highlighting admirable qualities in men. These findings shed light on the complex dynamics of gender portrayal within cultural proverbs, emphasizing the need for further examination of these linguistic expressions.